On-chip Energy Harvesting for Implantable Medical Devices - Stopjakova, Viera; Kovac, Martin; Potocny, Miroslav (Společnost pro radioelektronické inženýrství, 2020)
The paper brings an overview of main challenges in implantable medical devices (IMD) research area, where the main objective of discussion covers wireless power transferring (WPT) systems as the hot topic dedicated to energy harvesting that is still gaining in popularity. The paper is focused on electromagnetic-transfer principle, where full integration of the WPT systems on a chip is taken as the primary goal covering passive transducer and rectifier implementations. The presented research reveals many issues raised from the state of the art solutions. These solutions can or should be detailed investigated in the future research. Therefore, this paper discusses about so far hidden potential of fully integrated WPT systems, where both near-field and far-field approaches are included. Additionally, the discussion is also extended to a principle of power transfer efficiency (PTE) maximization through approaches such as matching and finding the optimal source/load together with rectifying and regulating issues.
Keywords: Wireless power transferring systems; energy harvesting; on-chip WPT implementation; electromagnetic-transfer principle; on-chip antennas